Suživot negatorijske zaštite od imisija i prava na život u zdravoj životnoj sredini - Mihelčić, Gabrijela (Array, 2018)
The authors analyse the national protection from emissions, in the first place, a property law component of this regime. Domestic regulation of the protection of property rights from harassment was brought in the perspective of the protection that the European Court of Human Rights provides for the right to live in a healthy environment, primarily through the protection of rights under Art. 8 of the Convention for the Protection of Human Rights and Fundamental Freedoms (right to respect for private and family life and home). In the context of the latter, the authors have analysed the interpretative methods used by the European Court and explored the following features: the requirement that environmental and environmental impacts and disturbances violate the Convention right, that is, the existence of a specific Convention causal link; the category of minimum level of severity; oscillation of the "quantum" of minimum level of severity within conventional "fluctuations"; and the scope (and type) of protecting the right to live in a healthy environment through the paradigm of the positive / negative obligations of the Contracting States.